Seroprevalence of toxoplasmosis between aborted ladies in Atbara district, Sudan - Rayan Khalid Mohamed Taha; Mosab Nouraldein Mohammed Hamad; Khalid Mohamed Taha; Ali Elamin Nasir Hamad (جامعة الشيخ عبدالله البدري, 2019)
Abstract Background: Toxoplasma gondii is an oblige intracellular protozoan parasite leading to toxoplasmosis in animals and humans. Principal maternal infection with toxoplasmosis throughout pregnancy is frequently associated with vertical transmission to the fetus. However it is not convinced whether Toxoplasma infection can cause frequent abortion. Justification: There is no formerly published data about the occurrence of toxoplasmosis between aborted women in Atbara district. Objectives: To recognize the Seroprevalence of toxoplasmosis among aborted women in Atbara district Method: Cross sectional, descriptive study, 152 aborted women from Atbara district were examined for anti-Toxoplasma gondii antibodies, three diagnostic techniques were used (latex agglutination, ICT and ELISA). Result: Generally the Seroprevalence rate of Toxoplasma parasite between aborted women according to the techniques used; 33.6 % by latex agglutination, 22.4 % by ICT and 35.5 % by ELISA method. Conclusion: The study conclude that there was high prevalence of toxoplasmosis among the participants and indicated that ELISA is the best serological method for detection of Toxoplasma gondii infection.